Predicting the propagation of acoustic waves using deep convolutional neural networks. (10th November 2021) - Alguacil, Antonio; Bauerheim, Michaël; Jacob, Marc C.; Moreau, Stéphane
Abstract: A novel approach for numerically propagating acoustic waves in two-dimensional quiescent media has been developed through a fully convolutional multi-scale neural network following a spatio-temporal auto-regressive strategy. This data-driven method managed to produce accurate results for long simulation times with a database of Lattice Boltzmann temporal simulations of propagating Gaussian Pulses, even in the case of initial conditions unseen during training time, such as the plane wave configuration or the two initial Gaussian pulses of opposed amplitudes. Two different choices of optimization objectives are compared, resulting in an improved prediction accuracy when adding the spatial gradient difference error to the traditional mean squared error loss function. Further accuracy gains are observed when performing an a posteriori correction on the neural network prediction based on the conservation of acoustic energy, indicating the benefit of including physical information in data-driven methods. Finally, the method is shown to be capable of relaxing the classical time-step constraint of LBM and to provide parallel properties suitable for accelerating significantly acoustic propagation simulations.